Alterations of Phosphodiesterases in Adrenocortical Tumors - Hannah-Shmouni, Fady; Faucz, Fabio R.; Stratakis, Constantine A. (Frontiers in Endocrinology, 2016)
Alterations in the cyclic (c) AMP-dependent signaling pathway have been implicated in the majority of benign adrenocortical tumors (ACTs) causing Cushing syndrome (CS). Phosphodiesterases (PDEs) are enzymes that regulate cyclic nucleotide levels, including cAMP. Inactivating mutations and other functional variants in PDE11A and PDE8B, two cAMP-binding PDEs, predispose to ACTs. The involvement of these two genes in ACTs was initially revealed by a genome-wide association study in patients with micronodular bilateral adrenocortical hyperplasia. Thereafter, PDE11A or PDE8B genetic variants have been found in other ACTs, including macronodular adrenocortical hyperplasias and cortisol-producing adenomas. In addition, down-regulation of PDE11A expression and inactivating variants of the gene have been found in hereditary and sporadic testicular germ cell tumors, as well as in prostatic cancer. PDEs confer an increased risk of ACT formation probably through, primarily, their action on cAMP levels, but other actions might be possible. In this report, we review what is known to date about PDE11A and PDE8B and their involvement in the predisposition to ACTs.